PERBANDINGAN ANTARA KOMPRES PARUTAN BAWANG MERAH DENGAN AIR HANGAT TERHADAP PENURUNAN SUHU TUBUH ANAK DEMAM DI PMB RUSMINI TAHUN 2023 - Imroatul Azizah; Rusmini Rusmini (STIKES Panca Bhakti Pontianak, 2024)
Fever is a condition where body temperature increases. If not treated quickly and appropriately, it will cause complications such as hyperthermia, seizures, and decreased consciousness. One way to lower body temperature in children with fever is non-pharmacological measures by providing grated shallot compresses and warm water compresses. The purpose of this study was to determine the effectiveness of grated shallot compresses and warm water compresses on reducing body temperature in children. The design of this study was Quasi Experiment with a Pre-testPost-test approach. The sampling method was carried out by Purposive Sampling with a sample size of 60 children. The sample was divided into 2 groups. 30 people in the grated shallot compress group, and 30 people in the warm water compress group. The data collection technique used a questionnaire sheet and a body temperature observation sheet. The analysis used was the Paired T-Test with a significance limit = <0.05. The results of this study indicate that grated shallot compresses can lower body temperature (P <0.000). Meanwhile, warm water compresses are also able to lower body temperature (P < 0.000). The Independent T-Test showed that there was a significant difference in effectiveness between red shallot compresses and warm water compresses where the decrease in temperature in grated shallot compresses (1.00) was greater than warm water compresses (0.44). The results of this study found that grated shallot compresses were more effective in lowering body temperature than warm air compresses.